TALLER DE JUEGOS DIDÁCTICOS PARA MEJORAR LA MOTRICIDAD FINA EN NIÑAS DE 4 AÑOS DE LA INSTITUCIÓN EDUCATIVA 18288 ISABEL LINCH DE RUBIO CHACHAPOYAS 2023 - Barrientos Yalta, María Sara (2023)
The present work entitled Didactic games workshops to improve fine motor skills in 4-year-old girls, this research was carried out with the objective of demonstrating how the didactic games workshop helps to improve fine motor skills in 4-year-old girls. The research was of a pre-experimental type within the approach, a sample of 28 4-year-old girls was carried out with the checklist and rubric. The results show that in the level of the acquired results of the girls of 4 years old in the classroom "Las Begonias" of the I.E 18288 "Isabel Lynch de Rubio" - Chachapoyas 2023, in fine motor skills, the results of the pre-test show that 28 girls are in the beginning level, which is equivalent to 100% of the total number of girls. On the other hand, in the post-test a difference is observed since we do not have any girl in the beginning level, 12 are in the process level, equivalent to 44.4%, 9 girls are in the achieved level, equivalent to 33.3% and finally 6 girls are in the outstanding level, equivalent to 22.2% of the total number of girls in this educational institution. In conclusion, the didactic games workshops help the development of fine motor skills where it can be seen that the girls perform effectively, since different ways of working are presented, many of them help to achieve the relevant development of their fine motor skills, as this can be evidenced in the results.